Предмет: Алгебра, автор: Аноним

Пожалуйста!!!

ВО ВЛОЖЕНИИ!!

Приложения:

Ответы

Автор ответа: Yena
0

frac{x^3+y^3}{x+y}:(x^2-y^2)+frac{2y}{x+y}-frac{xy}{x^2-y^2}=

=frac{(x+y)(x^2-xy+y^2)}{(x+y)(x^2-y^2)}+frac{2y}{x+y}-frac{xy}{x^2-y^2}=

=frac{x^2-xy+y^2+2xy-2y^2-xy}{x^2-y^2}=frac{x^2-y^2}{x^2-y^2}=1

/////////////////////////////////////////////////////////////////////////////////////////////////////////////

Автор ответа: mila66613
0

фывапролдэждлорпавыывапролдж

Приложения:
Похожие вопросы